A high-capacity Prussian blue positive electrode material and preparation method thereof

By pulverizing and deep drying, Prussian blue positive electrode material powder was treated, and a composite solution containing a reducing agent was used for repair in the co-precipitation method, the problem of hollow space generated during the co-precipitation method was solved, and the electrochemical performance of the material was significantly improved.

CN119118156BActive Publication Date: 2025-04-08JIANGMEN KANHOO IND CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411589352.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-04-08
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The existing Prussian blue cathode materials are prone to vacancy during the synthesis of co-precipitation method, resulting in a decrease in sodium content and capacity, which is difficult to effectively solve in industrial production.

Method used

By crushing the Prussian blue positive electrode material into a powder with a uniform particle size and drying it deeply, the moisture occupancy is reduced; a composite solution containing a reducing agent is used for repair treatment, and by reducing the trivalent iron ions to divalent iron ions, the positive charge concentration is reduced and the sodium ions are increased.

Benefits of technology

It improves the degree of vacancy repair and electrochemical performance of the material, and enhances the capacity and rate performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118156B_ABST
    Figure CN119118156B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of new energy, and discloses a high-capacity Prussian blue positive electrode material and a preparation method thereof, the method comprising the following steps: step 1: crushing the dried Prussian blue positive electrode material into a positive electrode material powder with uniform particle size; step 2: secondary drying the positive electrode material powder; step 3: reacting the dried positive electrode material powder with a composite solution; step 4: washing and drying the product obtained by the reaction in step 3; the composite solution contains sodium ferrocyanide and a reducing agent. The present invention crushes the positive electrode material into a powder with uniform particle size and fully dries it, thereby reducing the occupation of vacancies by water molecules and improving the degree of repair of the material; by using a composite solution containing a reducing agent for repair treatment, the reducing agent reduces the trivalent iron ions in the powder into divalent iron ions, reduces the positive charge concentration of the powder body, allows more sodium ions to enter the structure, and improves the material performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy, and particularly to a high-capacity Prussian blue-based cathode material and a preparation method thereof. Background Art

[0002] Prussian blue-based cathode materials are one of the mainstream cathode materials for sodium-ion batteries, having the advantages of high capacity and long cycle life. Their chemical formula can be written as Na2M[Fe(CN)6] x ·A y , where M can be one or more of Fe, Mn, Co, Ni, Cu, A represents the vacancies generated during the material synthesis, 0 < x ≤ 1, and x + y = 1. The synthesis of Prussian blue-based cathode materials generally adopts hydrothermal method, solid-phase method, coprecipitation method, etc. The hydrothermal method will generate toxic and harmful cyanide gas, which is not suitable for industrial production. The solid-phase method has many vacancies, small particles and low controllability in the product, and is also not suitable for industrial production. The coprecipitation method has the advantages of low cost and high controllability in the production process, and is very suitable for industrial scale-up production and is the most mainstream synthesis method. However, the coprecipitation method is carried out in an aqueous environment for synthesis, and inevitably generates vacancies, which are occupied by water molecules, and the transition metal elements are oxidized by oxygen in the water, resulting in a decrease in the sodium content of the material and a decrease in the capacity. Therefore, scientific researchers need to find an experimental method to fill the vacancies and improve the electrochemical performance of the material.

[0003] Prior Art: Publication No. CN113353955 B, with the theme of a Prussian blue and its analogues, a defect repair method and its application, proposes a vacancy defect repair method, which uses ferrocyanide to repair the [Fe(CN)6] 4- vacancy defects in traditional Prussian blue and its analogues.

[0004] This method has been verified and there is still room for further repair and improvement.

[0005] The technical problem to be solved in this case is: how to further improve the repair degree of the vacancy defects of traditional Prussian blue. Summary of the Invention

[0006] The purpose of the present invention is to provide a preparation method of a high-capacity Prussian blue-based cathode material. The present invention reduces the occupation of water molecules on the vacancies by crushing the cathode material into powders with uniform particle size and fully drying, thereby improving the repair degree of the material; by using a composite solution containing a reducing agent for repair treatment, the reducing agent reduces the trivalent iron ions in the powder to divalent iron ions, reduces the positive charge concentration of the powder body, enables more sodium ions to enter the structure, and improves the material performance.

[0007] At the same time, the present invention also provides the Prussian blue-based cathode material.

[0008] The specific scheme of the present invention is:

[0009] A method for preparing a high-capacity Prussian blue positive electrode material comprises the following steps:

[0010] Step 1: crushing the dried Prussian blue cathode material into cathode material powder with uniform particle size;

[0011] Step 2: performing secondary drying on the positive electrode material powder to obtain dried positive electrode material powder;

[0012] Step 3: reacting the dried positive electrode material powder with the composite solution;

[0013] Step 4: washing and drying the product obtained by the reaction in step 3 to obtain a high-capacity Prussian blue positive electrode material;

[0014] The composite solution contains sodium ferrocyanide and a reducing agent.

[0015] The present invention improves the uniformity of particle size, so that the moisture of the powder after secondary drying is removed more evenly and thoroughly, which is beneficial to the uniformity and degree of vacancy repair in the later stage, makes the product uniformity of the positive electrode material better, and improves the electrochemical performance;

[0016] The present invention uses a composite solution containing a reducing agent to achieve the reduction of trivalent iron in the positive electrode material powder, so that more sodium ions are embedded in the structure, thereby improving the material capacity and rate performance.

[0017] At the same time, the present invention has also tested the method of first reducing and then repairing, which cannot achieve a good repair effect, indicating that the simultaneous repair and reduction is necessary. The reason for the poor effect of first reducing and then repairing is that: in the repair process, accompanied by a certain degree of redox reaction, and after the positive electrode material surface is exposed to air after reduction, some ferrous ions will be rapidly oxidized. Therefore, the use of repair and reduction synchronously can effectively improve product performance.

[0018] In the above-mentioned preparation method, the composite solution is a saturated solution of sodium ferrocyanide; the content of the reducing agent in the composite solution is 0.005-0.2 mol / L.

[0019] In the above preparation method, the reducing agent is one or more combinations of sodium borohydride, sodium thiosulfate, sodium hypophosphite, ascorbic acid, and sodium iodide.

[0020] In the above preparation method, the drying temperature of step 1 is 70-120° C.; the drying temperature of step 2 is 180-210° C.; and both steps 1 and 2 are dried in the absence of oxygen.

[0021] In the above preparation method, the drying time of step 1 is 15 to 20 hours; the drying time of step 2 is 4 to 8 hours.

[0022] In the present invention, step 1 is dried at low temperature and step 2 is dried at high temperature. The advantage of this operation mode is that low-temperature drying is first performed to remove free water in the material, which can make the material drying more uniform and prevent the liquid from boiling and splashing the material. Since step 1 is finally crushed, the particles are fully exposed, ensuring that when a higher temperature is used for heating in step 2, the particles can be heated evenly, and the crystal water occupying the vacant positions can be better and thoroughly removed, and the material consistency is better.

[0023] In the above preparation method, in step 1, the D50 particle size of the pulverized positive electrode material powder is 3-15 μm, the particle size distribution diagram is a single peak, the diameter distance (SPAN) is 0.7-0.9, and the specific surface area is 0.500-3.000 m 2 / g.

[0024] In the present invention, a suitable particle size is more conducive to further improvement of performance. During the production process, if the particle size is too large, the inner layer of moisture in the product cannot be fully removed, the material consistency is poor, the inner layer vacancy repair is incomplete, the electrochemical performance is poor, and other problems will occur. If the particle size is too small, the particles will clump together, resulting in poor dispersion, making post-processing difficult, and affecting the structural stability of the products prepared later, thereby affecting the electrochemical performance.

[0025] In the above-mentioned preparation method, in step 1, the preparation method of the dried Prussian blue positive electrode material is:

[0026] Deionized water is added to a reaction container, and a sodium ferrocyanide solution and a metal source solution are added to the reaction container, and the reaction is carried out in an inert gas environment. After the reaction is completed, the solution is aged for a period of time and washed and dried;

[0027] The metal source solution contains metal salt and sodium citrate; the metal salt is one or more of soluble iron salt, manganese salt, cobalt salt, nickel salt and copper salt.

[0028] In the above preparation method, the molar ratio of sodium ferrocyanide in the sodium ferrocyanide solution, the metal salt in the metal source solution, and sodium citrate is 0.9-1.1:1:3.

[0029] In the above preparation method, the reaction time of step 3 is 6 to 12 hours;

[0030] The washing and drying operations in step 4 are as follows:

[0031] The deoxygenated ethanol and water mixture is centrifuged and washed once or multiple times to obtain a precipitate, and the precipitate is placed in a vacuum environment at 70 to 120° C. and dried for 15 to 20 hours.

[0032] The concentration of ethanol in the ethanol-water mixture is 40~70vol%;

[0033] The washing frequency is generally 2 to 4 times.

[0034] At the same time, the present invention also discloses a high-capacity Prussian blue positive electrode material, which is prepared by any of the above methods.

[0035] The beneficial effects of this application are:

[0036] The core invention of the present invention is to use uniform positive electrode material powder for deep drying to improve the uniformity of particle size and water removal, and to use a reducing agent for auxiliary reduction during vacancy repair to improve the vacancy repair effect;

[0037] Through the above measures, the degree of vacancy repair can be effectively improved and the electrochemical performance can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is an electron microscope photograph of the product of Example 1 of the present invention. DETAILED DESCRIPTION

[0039] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. In the description of the present invention, it should be noted that, if no specific conditions are specified in the embodiments, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0040] Example 1

[0041] 1. Place 200 mL of deionized water in a four-necked flask as the base solution, and continue to pass nitrogen into the water for two hours to replace the oxygen in the water while keeping stirring;

[0042] 2. Dissolve 0.168 mol sodium ferrocyanide in 323 mL deionized water to obtain solution A; dissolve 0.160 mol ferrous chloride and 0.480 mol sodium citrate in 320 mL deionized water to obtain solution B;

[0043] 3. Add solution A and B to the bottom solution through a peristaltic pump, react at room temperature to generate a Prussian blue cathode material, and age for 3 hours after the addition is completed;

[0044] 4. Wash the samples after aging by centrifugation three times with a deoxygenated ethanol and water mixture (ethanol concentration is 40 vol%), and finally put the precipitate into a vacuum drying oven for vacuum drying at 70°C for 15 hours;

[0045] 5. After the fourth step of vacuum drying, the material is crushed and dispersed (the average particle size after crushing is 10μm), and then vacuum dried again at 180℃ for 4 hours;

[0046] 6. Add the dried material from step 5 to the composite solution at a constant temperature of 50°C and continue stirring for 6 hours; add 28g of the dried material from step 5 to every 100ml of the composite solution;

[0047] The composite solution is a saturated solution of sodium ferrocyanide and contains 0.005 mol / L of reducing agent sodium borohydride;

[0048] 7. Wash the sample after the reaction in step 6 by centrifugation three times with a deoxygenated ethanol and water mixture (ethanol concentration is 70 vol%). Finally, place the precipitate in a vacuum drying oven and vacuum dry it at 70°C for 15 hours to obtain a Prussian blue cathode material filled with vacancies and high in sodium ions. The microscopic photo shows Figure 1 .

[0049] Example 2

[0050] The process is substantially the same as in Example 1, except that the reducing agent in step 6 is sodium thiosulfate with a concentration of 0.01 mol / L.

[0051] Example 3

[0052] The process is substantially the same as in Example 1, except that the reducing agent in step 6 is sodium hypophosphite with a concentration of 0.2 mol / L.

[0053] Example 4

[0054] The process is substantially the same as in Example 1, except that the drying temperature in step 4 is 90° C. and the drying time is 18 h; the drying temperature in step 5 is 195° C. and the drying time is 6 h.

[0055] Example 5

[0056] The process is substantially the same as in Example 1, except that the drying temperature in step 4 is 120° C. and the drying time is 20 h; the drying temperature in step 5 is 210° C. and the drying time is 8 h.

[0057] Example 6

[0058] The method is substantially the same as Example 1, except that the average particle size after crushing in step 5 is 3 μm.

[0059] Example 7

[0060] The method is substantially the same as Example 1, except that the average particle size after crushing in step 5 is 15 μm.

[0061] Comparative Example 1

[0062] 1. Place 200 mL of deionized water in a four-necked flask as the base solution, and continue to pass nitrogen into the water for two hours to replace the oxygen in the water while keeping stirring;

[0063] 2. Dissolve 0.168 mol sodium ferrocyanide in 323 mL deionized water to obtain solution A; dissolve 0.160 mol ferrous chloride and 0.480 mol sodium citrate in 320 mL deionized water to obtain solution B;

[0064] 3. Add solution A and solution B to the bottom solution through a peristaltic pump to react and generate a Prussian blue cathode material. After the addition is completed, age for 3 hours;

[0065] 4. Wash the samples after aging by centrifuging them three times with a deoxygenated ethanol and water mixture (ethanol concentration is 40 vol%). Finally, place the precipitate in a vacuum drying oven and vacuum dry it at 70°C for 15 hours to obtain a Prussian blue positive electrode material.

[0066] Comparative Example 2

[0067] 1. Place 200 mL of deionized water in a four-necked flask as the base solution, and continue to pass nitrogen into the water for two hours to replace the oxygen in the water while keeping stirring;

[0068] 2. Dissolve 0.168 mol sodium ferrocyanide in 323 mL deionized water to obtain solution A. Dissolve 0.160 mol ferrous chloride and 0.480 mol sodium citrate in 320 mL deionized water to obtain solution B.

[0069] 3. Add solution A and solution B to the bottom solution through a peristaltic pump to react and generate a Prussian blue cathode material. After the addition is completed, age for 3 hours;

[0070] 4. Wash the samples after aging by centrifugation three times with a deoxygenated ethanol and water mixture (ethanol concentration is 40 vol%), and finally put the precipitate into a vacuum drying oven for vacuum drying at 70°C for 15 hours;

[0071] 5. Add the dried material in step 4 into a composite solution consisting of a saturated sodium ferrocyanide solution and a 0.005 mol / L sodium borohydride solution at a constant temperature of 50°C, and continue stirring for 6 hours;

[0072] 6. Wash the sample after the reaction by centrifuging it three times with a deoxygenated ethanol and water mixture (ethanol concentration is 70 vol%). Finally, place the precipitate in a vacuum drying oven and vacuum dry it at 70°C for 15 hours to obtain a Prussian blue positive electrode material.

[0073] Comparative Example 3

[0074] 1. Place 200 mL of deionized water in a four-necked flask as the base solution, and continue to pass nitrogen into the water for two hours to replace the oxygen in the water while keeping stirring;

[0075] 2. Dissolve 0.168 mol sodium ferrocyanide in 323 mL deionized water to obtain solution A. Dissolve 0.160 mol ferrous chloride and 0.480 mol sodium citrate in 320 mL deionized water to obtain solution B.

[0076] 3. Add solution A and solution B to the bottom solution through a peristaltic pump to react and generate a Prussian blue cathode material. After the addition is completed, age for 3 hours;

[0077] 4. Wash the samples after aging by centrifugation three times with a deoxygenated ethanol and water mixture (ethanol concentration is 40 vol%), and finally put the precipitate into a vacuum drying oven for vacuum drying at 70°C for 15 hours;

[0078] 5. After the fourth step of vacuum drying, the material is crushed and dispersed to an average particle size of 3 μm, and then vacuum dried again at 180°C for 4 hours to remove the water molecules occupying the vacancies in the material and obtain a Prussian blue positive electrode material.

[0079] Comparative Example 4

[0080] 1. Place 200 mL of deionized water in a four-necked flask as the base solution, and continue to pass nitrogen into the water for two hours to replace the oxygen in the water while keeping stirring;

[0081] 2. Dissolve 0.168 mol sodium ferrocyanide in 323 mL deionized water to obtain solution A; dissolve 0.160 mol ferrous chloride and 0.480 mol sodium citrate in 320 mL deionized water to obtain solution B;

[0082] 3. Add solution A and solution B to the bottom solution through a peristaltic pump to react and generate a Prussian blue cathode material. After the addition is completed, age for 3 hours;

[0083] 4. Wash the samples after aging by centrifugation three times with a deoxygenated ethanol and water mixture (ethanol concentration is 40 vol%), and finally put the precipitate into a vacuum drying oven for vacuum drying at 70°C for 15 hours;

[0084] 5. After the fourth step of vacuum drying, the material is crushed and dispersed (the average particle size after crushing is 3μm), and then vacuum dried again at 180℃ for 4 hours to remove the water molecules occupying the vacancies in the material;

[0085] 6. Add the dried material from step 5 into a saturated sodium ferrocyanide solution at 50°C and continue stirring for 6 hours;

[0086] 7. Wash the sample after the reaction by centrifuging it three times with a deoxygenated ethanol and water mixture (ethanol concentration is 70 vol%). Finally, place the precipitate in a vacuum drying oven and vacuum dry it at 70°C for 15 hours to obtain a Prussian blue positive electrode material.

[0087] Comparative Example 5

[0088] 1. Place 200 mL of deionized water in a four-necked flask as the base solution, and continue to pass nitrogen into the water for two hours to replace the oxygen in the water while keeping stirring;

[0089] 2. Dissolve 0.168 mol sodium ferrocyanide in 323 mL deionized water to obtain solution A; dissolve 0.160 mol ferrous chloride and 0.480 mol sodium citrate in 320 mL deionized water to obtain solution B;

[0090] 3. Add solution A and solution B to the bottom solution through a peristaltic pump to react and generate a Prussian blue cathode material. After the addition is completed, age for 3 hours;

[0091] 4. Wash the samples after aging by centrifugation three times with a deoxygenated ethanol and water mixture (ethanol concentration is 40 vol%), and finally put the precipitate into a vacuum drying oven for vacuum drying at 70°C for 15 hours;

[0092] 5. After the fourth step of vacuum drying, the material is crushed and dispersed (the average particle size after crushing is 6μm), and then vacuum dried again at 180℃ for 4 hours to remove the water molecules occupying the vacancies in the material;

[0093] 6. Add the dried material from step 5 into a 0.005 mol / L reducing agent sodium borohydride solution at a constant temperature of 50°C and continue stirring for 16 hours;

[0094] 7. Wash the sample after the reaction by centrifuging it three times with a deoxygenated ethanol and water mixture (ethanol concentration is 70 vol%). Finally, place the precipitate in a vacuum drying oven and vacuum dry it at 70°C for 15 hours to obtain a Prussian blue positive electrode material.

[0095] Comparative Example 6

[0096] 1. Place 200 mL of deionized water in a four-necked flask as the base solution, and continue to pass nitrogen into the water for two hours to replace the oxygen in the water while keeping stirring;

[0097] 2. Dissolve 0.168 mol sodium ferrocyanide in 323 mL deionized water to obtain solution A; dissolve 0.160 mol ferrous chloride and 0.480 mol sodium citrate in 320 mL deionized water to obtain solution B;

[0098] 3. Add solution A and B to the bottom solution through a peristaltic pump, react at room temperature to generate a Prussian blue cathode material, and age for 3 hours after the addition is completed;

[0099] 4. Wash the samples after aging by centrifugation three times with a deoxygenated ethanol and water mixture (ethanol concentration is 40 vol%), and finally put the precipitate into a vacuum drying oven for vacuum drying at 70°C for 15 hours;

[0100] 5. After the fourth step of vacuum drying, the material is crushed and dispersed (the average particle size after crushing is 6μm), and then vacuum dried again at 180℃ for 4 hours;

[0101] 6. Add the dried material in step 5 into a reducing agent solution (containing 0.005 mol / L sodium borohydride) at a constant temperature of 50°C and continue stirring for 6 hours; then filter the reaction product and vacuum dry it at 70°C for 12 hours;

[0102] Then the dried powder was added into a saturated solution of sodium ferrocyanide and reacted for 6 hours;

[0103] Add 28g of the dried material from step 5 to every 100ml of reducing agent solution; add 28g of the reduced powder to every 100ml of saturated sodium ferrocyanide solution;

[0104] 7. Wash the sample after the reaction in step 6 by centrifuging it three times with a deoxygenated ethanol and water mixture (ethanol concentration is 70 vol%). Finally, place the precipitate in a vacuum drying oven and vacuum dry it at 70°C for 15 hours to obtain a Prussian blue positive electrode material.

[0105] Test part:

[0106] Test items include: sodium content, vacancy concentration, 0.1C charge specific capacity, capacity retention rate;

[0107] The detection methods for the above items are:

[0108] Sodium content: Inductively coupled plasma test (ICP test);

[0109] Vacancy concentration: The carbon-sulfur analyzer characterizes the C content as c0, and then calculates the amount of vacancies using the formula 1-c0*313.8 / (12.01*6).

[0110] 0.1C charge ratio capacity and capacity retention rate: After assembling and de-energizing, the charge and discharge test is carried out in the Xinwei test cabinet, and the capacity retention rate is the data of 1C cycle 100 weeks.

[0111] The test results refer to Table 1:

[0112] Table 1

[0113] Sodium content (%) Vacancies 0.1C charging capacity (mAh / g) Capacity retention rate (%) Example 1 18.97 0.04 164 95 Example 2 18.63 0.04 158 94 Example 3 18.70 0.04 159 95 Example 4 18.96 0.04 164 95 Example 5 18.95 0.04 164 95 Example 6 18.95 0.03 167 92 Example 7 18.86 0.04 160 98 Comparative Example 1 17.53 0.14 143 78 Comparative Example 2 18.18 0.09 153 87 Comparative Example 3 17.55 0.14 142 78 Comparative Example 4 15.74 0.04 128 91 Comparative Example 5 18.03 0.14 148 79 Comparative Example 6 16.59 0.11 136 83

[0114] Result analysis:

[0115] 1. It can be seen from Examples 1 to 7 that the finished product has a low vacancy content and a high sodium content, which can effectively improve the electrochemical performance of the positive electrode material;

[0116] 2. By comparing Example 1 with Comparative Examples 1 to Comparative Examples 6, it can be seen that the sodium content is low, the vacancy concentration is high, and the electrochemical performance is obviously inferior to that of Example 1. The reason is:

[0117] Comparative Example 1 only synthesized a Prussian blue positive electrode material, in which a large number of vacancies occupied by water existed, which reduced the sodium content of the positive electrode material and reduced the electrochemical performance;

[0118] Although Comparative Example 2 used a reducing agent and sodium ferrocyanide to try to compete for the vacancy occupied by water, compared with Comparative Example 1, it had a slight effect, but the effect was not significant;

[0119] Comparative Example 3 adopts a crushing and drying operation, which is only used to evenly remove moisture and eliminate vacancies occupied by moisture, but does not fill the vacancies with sodium ions. Therefore, its electrochemical performance is similar to or even the same as that of Comparative Example 1.

[0120] Although Comparative Example 4 uses pulverization to remove vacancies occupied by water molecules, in the absence of a reducing agent, the saturated sodium ferrocyanide solution added in step 6 inevitably contains oxygen, which will convert a small amount of ferrous iron into ferric iron. At the same time, the most important thing is that the addition of sodium ferrocyanide will increase the proportion of iron ions in the positive electrode, which will be manifested as a sharp decrease in the content of sodium ions. However, this case is not without benefits. Compared with Comparative Example 3, its capacity retention performance is improved. From one aspect, adding sodium ferrocyanide to the pulverized and dried positive electrode material can improve the capacity retention performance.

[0121] Comparative Example 5 uses a reducing agent, but does not use sodium ferrocyanide. The reducing agent can reduce trivalent iron, and at the same time, it can itself replenish sodium ions into the positive electrode material to a limited extent, which ultimately manifests as an increase in the sodium content.

[0122] Comparative Example 6 adopts the operation of reducing first and then reacting with sodium ferrocyanide. Its result is similar to that of Comparative Example 4. During the reduction process of the reducing agent, the water molecules in the solution re-occupy the vacant positions, resulting in [Fe(CN)6]4+ being unable to occupy the defective positions when added to the saturated sodium ferrocyanide solution in the next step, resulting in a significant reduction in the degree of repair. The reason for the decrease in sodium ion content is similar to that of Comparative Example 4.

[0123] The following conclusions can be drawn from the above experiments:

[0124] By improving the uniformity of particle size, the moisture of the powder after secondary drying can be removed more evenly and thoroughly, which is beneficial to the uniformity and degree of vacancy repair in the later stage, making the product uniformity of the positive electrode material better and improving the electrochemical performance;

[0125] By using a composite solution containing a reducing agent, the reduction of trivalent iron in the positive electrode material powder can be achieved, so that more sodium ions can be embedded in the structure, thereby improving the material capacity and rate performance.

Claims

1. A method for preparing a high-capacity Prussian blue positive electrode material, characterized in that: The steps include: Step 1: crushing the dried Prussian blue cathode material into cathode material powder with uniform particle size; Step 2: performing secondary drying on the positive electrode material powder to obtain dried positive electrode material powder; Step 3: reacting the dried positive electrode material powder with the composite solution; Step 4: washing and drying the product obtained by the reaction in step 3 to obtain a high-capacity Prussian blue positive electrode material; The composite solution contains sodium ferrocyanide and a reducing agent, and the composite solution is a saturated solution of sodium ferrocyanide; the content of the reducing agent in the composite solution is 0.005-0.2 mol / L; the drying temperature of step 1 is 70-120° C.; the drying temperature of step 2 is 180-210° C.; both steps 1 and 2 are dried in the absence of oxygen; In step 1, the D50 particle size of the pulverized positive electrode material powder is 3-15 μm, the particle size distribution diagram is a single peak, the diameter distance is 0.7-0.9, and the specific surface area is 0.500-3.000 m 2 / g; In the step 1, the preparation method of the dried Prussian blue positive electrode material is: Deionized water is added to a reaction container, and a sodium ferrocyanide solution and a metal source solution are added to the reaction container, and the reaction is carried out in an inert gas environment. After the reaction is completed, the solution is aged for a period of time and washed and dried; The metal source solution contains metal salt and sodium citrate; the metal salt is one or more of soluble iron salt, manganese salt, cobalt salt, nickel salt and copper salt; the molar ratio of sodium ferrocyanide in the sodium ferrocyanide solution, the metal salt in the metal source solution and sodium citrate is 0.9-1.1:1:

3.

2. The preparation method according to claim 1, characterized in that: The reducing agent is one or more combinations of sodium borohydride, sodium thiosulfate, sodium hypophosphite, ascorbic acid and sodium iodide.

3. The preparation method according to claim 1, characterized in that: The drying time of step 1 is 15 to 20 hours; the drying time of step 2 is 4 to 8 hours.

4. The preparation method according to claim 1, characterized in that: The reaction time of step 3 is 6 to 12 hours; The washing and drying operations in step 4 are as follows: The deoxygenated ethanol and water mixture is centrifuged and washed once or multiple times to obtain a precipitate, and the precipitate is placed in a vacuum environment at 70 to 120° C. and dried for 15 to 20 hours.

5. A high-capacity Prussian blue positive electrode material, characterized in that: The method is prepared by any one of claims 1 to 4.

Citation Information

Patent Citations

  • A Prussian blue and its analogues, a defect repair method and its application

    CN113353955B

  • Hollow iron-based Prussian blue and template-free preparation method and application thereof

    CN117902596A